Յոթներգություն կամ ծիածանի հազար ու մեկ գույնը - Հակոբյան, Վարդան («Դիզակ պլյուս» հրատարակչություն)
В статье рассматривается значимость книги ливанского армянина, поэта, литературоведа и переводчика Саркиса Киракосяна "Радуга кедров", включающая переводы современных арабских поэтов. The article reveals the significance of "The Rainbow of Cedars” by Lebanese Armenian poet, literary critic and translator Sargis Kirakosyan. It includes the translations of contemporary Arabian poets.
Keywords: Գրականություն